2022
DOI: 10.1097/brs.0000000000004477
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Paraspinal Fatty Muscle Infiltration and Cumulative Lumbar Spine Degeneration on the Outcome of Patients with Lumbar Spinal Canal Stenosis: Analysis of the Lumbar Stenosis Outcome Study (LSOS) Data

Abstract: Study Design. Prospective. Objective. To investigate the influence of paraspinal fatty muscle infiltration (FMI) and cumulative lumbar spine degeneration as assessed by magnetic resonance imaging on long-term clinical outcome measures in patients with lumbar spinal canal stenosis (LSCS) of the Lumbar Stenosis Outcome Study (LSOS) cohort. Summary of Background Data. Past studies have tried to establish correlations of morphologic imaging findings in LSCS with clinical endpoints. However, the impact of FMI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The Goutallier classification serves as a widely used tool for evaluating fatty degeneration or infiltration of musculature, ( 20 , 21 ) particularly in conditions such as rotator cuff tears ( 22 , 23 ) and muscle atrophy. ( 24 , 25 ) Previous studies have shown the prognostic value of the Goutallier classification in clinical and radiologic outcome studies on the fatty infiltration of the rotator cuff musculature.…”
Section: Discussionmentioning
confidence: 99%
“…The Goutallier classification serves as a widely used tool for evaluating fatty degeneration or infiltration of musculature, ( 20 , 21 ) particularly in conditions such as rotator cuff tears ( 22 , 23 ) and muscle atrophy. ( 24 , 25 ) Previous studies have shown the prognostic value of the Goutallier classification in clinical and radiologic outcome studies on the fatty infiltration of the rotator cuff musculature.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that fatty infiltration of paraspinal muscles is associated with higher disability and poor health-related quality of life. [ 23 ] Zotti et al . demonstrated that less muscle mass of LM was correlated with worse outcome in patients who had decompression surgery for LSS.…”
Section: Discussionmentioning
confidence: 99%
“…Miki et al [8] used the NRS, RMDQ, and EQ-5D scales and found that a decreased MF CSA was associated with lower back pain. Getzmann, J.M., et al [22] found that fatty muscle infiltration was associated with higher rates of disability and worse HRQOL in patients with EQ-5D-3L scores. Han et al [23] found a significant correlation among paraspinal muscle endurance, VAS scores, and ODI scores in patients with LSS.…”
Section: Discussionmentioning
confidence: 99%